Enhancing ESP Students’ Reading Comprehension and Critical Thinking through Research Articles: Students’ Perspective - Yunika Triana; Pratomo Widodo; Kastam Syamsi; M. Ikhwan (Jurnal Ilmiah Peuradeun, 2026)
The increasing availability of digital knowledge resources has not been matched by the ability of students to engage effectively with academic texts in English for Specific Purposes (ESP) contexts. This study investigated how the use of research articles as core learning materials supported knowledge construction, enhanced critical thinking, fosters student independence, and examined the role of lecturer feedback as pedagogical scaffolding. Using a qualitative case study design, the research involved 34 second-semester students in a Sharia Economic Law program, with data collected through classroom observations and semi-structured interviews with seven purposively selected participants. Data were analyzed using Reflexive Thematic Analysis. The findings indicated that engagement with English-language research articles facilitates progressive knowledge construction through collaborative and independent learning processes. Group work enhanced idea exchange and comprehension, while individual tasks promoted deeper reflection and autonomy. Lecturer feedback played a crucial role in guiding analytical thinking and improving students’ evaluation of academic texts. This study highlighted the importance of integrating authentic materials, structured feedback, and balanced learning approaches to strengthen ESP students’ academic literacy and higher-order thinking skills.